PERANAN PENDIDIKAN DALAM MENINGKATKAN SUMBER DAYA MANUSIA DI SMA NEGERI 1 TAMPAN AMMA DI TALAUD - Halean, Stevi; Kandowangko, Nicholaas; Goni, Shirley Y. V. I. (Universitas Sam Ratulangi, 2021)
Education has a very important role in relation to the management and preservation of the environment and natural resources, education seeks to change the behavior of students in thinking and acting or acting. SMA N 1 Tampan Amma is one of the schools in Talaud that lacks educators willing to be placed in rural areas including islands / small. The first public school in Tampan Amma subdistrict and very far from the district capital, experienced problems that include weak quality of teaching staff, teachers who must meet professional requirements, teachers who must have a progressive nature, oriented to progress / renewal, always follow the development, and love to learn.In order to produce superior human resources. Involving the ideas of all educators in the commission session held at the beginning of the new learning year, representing the development of educators in SMA Negeri 1 Tampan Amma based on democratic values and nuances of justice and commitment to carry it out continuously. Such a situation, will trigger an increase in the competence of educators. In such conditions, the paradigm (insight) of the importance of professionalism will gradually form in the mindset and attitude patterns of educatorsThe role of education in improving human resources is needed by every student who attends education, the teachers at SMA N.1 Tampan Amma must also play an important role in improving the quality of teaching and learning of each student, in order to be able to produce the best graduates of the school and be able to compete with other schools.Â Keywords: education, role, human resources